Synthesis and properties of highly phenyl-substituted fluorene copolymers containing hole and electron transporting moieties via Diels-Alder polymerization - Suh, DH; Jung, SH; Park, SJ; Kim, DY; Cho, HN (TAYLOR & FRANCIS LTD, 2004)
Highly phenyl-substituted fluorene copolymers with hole and electron transporting moieties in the main chain were synthesized by using Diels-Alder polymerization. These polymers show good solubility in common organic solvents, high thermal stability, and strong blue photoluminescence in solid films. Cyclic voltammetry studies revealed that these polymers possess low-lying HOMO energy towels ranging from - 5.99 to - 6.00 eV.